2018
DOI: 10.1111/ijfs.14073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aleurone‐rich fraction on the hydration and rheological properties attributes of wheat dough

Abstract: This study aimed to evaluate the effects of incorporation of aleurone-rich fraction (ALF) on the hydration and rheological properties of wheat dough. Incorporation of ALF significantly increased water absorption (P < 0.05) and competition for water in dough was observed. Peak viscosity, through viscosity, and final viscosity decreased with the amount of ALF added (P < 0.05), whereas 20% ALF had stronger gel ability than whole-wheat flour. Dynamic rheological experiments revealed ALF blend dough were more stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…The quoted authors state that the addition of non-bread flours increases the hardness of bread crumb. According to Li et al [ 34 ], soluble fiber fractions (especially arabinoxylans) can increase the stability of the dough, because the fibers combine in the form of chains with other macromolecules. As a result, it probably increases the hardness of the crumb.…”
Section: Resultsmentioning
confidence: 99%
“…The quoted authors state that the addition of non-bread flours increases the hardness of bread crumb. According to Li et al [ 34 ], soluble fiber fractions (especially arabinoxylans) can increase the stability of the dough, because the fibers combine in the form of chains with other macromolecules. As a result, it probably increases the hardness of the crumb.…”
Section: Resultsmentioning
confidence: 99%
“…Components in cereal cell walls especially arabinoxylan showed significantly higher water solubility that leads to the increase in water absorption capacity of dough through addition in flour by chain linkages and chain solvent interactions of these nonstarch polysaccharides (Carvajal-Millan, Guigliarelli, Belle, Rouau, & Micard, 2005;Guo, Yang, & Zhu, 2018;Khan & Shewry, 2009;Sasaki, Kaoru, & Takeshi, 2004). As water absorption capacity is increased, it ultimately leads to the decrease in dough development time, mixing time and softness of dough and increase in dough stability, peak height and MTI (Li, Hu, & Xu, 2019). Saeed et al (2016) probed the effect of arabinoxylan addition on farinographic, mixographic, amylographic, and extensographic characteristics of wheat flour and found that addition of arabinoxylan increased the water absorption capacity, dough stability, maximum extensibility, load volume, and texture whereas, decreased the gelatinization and maximum resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Components in cereal cell walls especially arabinoxylan showed significantly higher water solubility that leads to the increase in water absorption capacity of dough through addition in flour by chain linkages and chain solvent interactions of these non‐starch polysaccharides (Carvajal‐Millan, Guigliarelli, Belle, Rouau, & Micard, 2005; Guo, Yang, & Zhu, 2018; Khan & Shewry, 2009; Sasaki, Kaoru, & Takeshi, 2004). As water absorption capacity is increased, it ultimately leads to the decrease in dough development time, mixing time and softness of dough and increase in dough stability, peak height and MTI (Li, Hu, & Xu, 2019). Saeed et al.…”
Section: Introductionmentioning
confidence: 99%
“…These rheological properties are improved through the addition of cell wall of different cereals and components of cell wall in cereal flour. Components in cereal cell walls, especially arabinoxylan, showed a significantly higher water solubility that leads to the increase in water absorption capacity of dough through addition in flour by chain linkages and chain solvent interactions of these nonstarch polysaccharides (Carvajal‐Millan, Guigliarelli, Belle, Rouau, & Micard, ; Khan & Shewry, ; Li et al, ; Sasaki, Kaoru, & Takeshi, ).…”
Section: Introductionmentioning
confidence: 99%